Loaded delta-hemolysin shapes the properties of Staphylococcus aureus membrane vesicles - Chen, Juan; Lv, Yuhuan; Shang, Weilong; Yang, Yi; Wang, Yuting; Hu, Zhen; Huang, Xiaonan; Zhang, Rong; Yuan, Jizhen; Huang, Jingbin; Rao, Xiancai (Frontiers in Microbiology, 2023)
Background: Membrane vesicles (MVs) are nanoscale vesicular structures produced by bacteria during their growth in vitro and in vivo. Some bacterial components can be loaded in bacterial MVs, but the roles of the loaded MV molecules are unclear.Methods: MVs of Staphylococcus aureus RN4220 and its derivatives were prepared.Dynamic light scattering analysis was used to evaluate the size distribution, and 4D-label free liquid chromatography-tandem mass spectrometry analysis was performed to detect protein composition in the MVs. The site-mutation S. aureus RN4220-Δhld and agrA deletion mutant RN4220-ΔagrA were generated via allelic replacement strategies. Hemolysis assay was performed with rabbit red blood cells.CCK-8 and lactate dehydrogenase release assays were used to determine the cytotoxicity of S. aureus MVs against RAW264.7 macrophages. The serum levels of inflammatory factors IL-6, IL-1β, and TNFα in mouse treated with S. aureus MVs were detected with an enzyme-linked immunosorbent assay kit.Results: Delta-hemolysin (Hld) was identified as a major loaded factor in S. aureus MVs. Further study showed that Hld could promote the production of staphylococcal MVs with smaller sizes. Loaded Hld affected the diversity of loaded proteins in MVs of S. aureus RN4220. Hld resulted in decreased protein diversity in MVs of S. aureus.Site-mutation (RN4220-Δhld) and agrA deletion (RN4220-ΔagrA) mutants produced MVs ( Δhld MVs and ΔagrA MVs) with a greater number of bacterial proteins than those derived from wild-type RN4220 ( wt MVs). Moreover, Hld contributed to the hemolytic activity of wt MVs. Hld-loaded wt MVs was cytotoxic to macrophage RAW264.7 cells and could stimulate the production of inflammatory factor IL-6 in vivo.This work presented that Hld was a major loaded factor in S. aureus MVs, and the loaded-Hld played vital roles in the MV-property modification.